Population dynamics of shrimp Pleoticus muelleri in an upwelling region and new implications for latitudinal gradient theories - Sancinetti, Gustavo S. [UNESP]; Castilho, Antônio L. [UNESP]; Wolf, Milena R. [UNESP]; Costa, Rogério C. [UNESP]; Azevedo, Alexandre; Fransozo, Adilson [UNESP] (Cambridge University Press (CUP), 2019)
The population dynamics of shrimp Pleoticus muelleri was used as a model to verify if the trend of continuous reproduction periodicity, shorter body size and longevity, and early sexual maturity found in tropical regions is corroborated in upwelling regions. Shrimps were sampled in a region under the influence of upwelling (northern coast of Rio de Janeiro State, Brazil). Characteristics of bottom water were registered, and shrimps were measured (carapace length - CL) and classified by sex and gonadal development stages. Reproduction was seasonal, from September to December, and favoured by water mass intrusions of low temperatures and high chlorophyll concentrations. The greatest number of reproductive females preceded periods with the highest chlorophyll concentrations in the water column (cross-correlation; P < 0.05, lag (month) = -3, r = 0.50), suggesting greater developmental success of larval stage due to increase of food availability. Von Bertalanffy growth models resulted in asymptotic carapace length estimates of CL∞ = 40.21 mm and CL∞ = 36.78 mm for females and males, respectively. The reproductive and growth characteristics of the P. muelleri population studied herein were similar to that of populations from higher latitudes, demonstrating that the latitudinal pattern rule cannot be applied in regions influenced by an upwelling phenomenon.
Keywords: Growth; lifespan; Penaeiodea; Western Atlantic Ocean